Penerapan Aplikasi Bordir Bermotif Naga Dan Burung Phoenix Pada Crinoline Gaun Choengsam - Azifah, Ni'matul; Arifiana, Deny (Institut Seni Indonesia Yogyakarta, 2024)
AbstractThis study aims to find out how the finished process of applying dragon and phoenix patterned embroidery applications to crinoline cheongsam dresses, and to find out the results of applying dragon and phoenix patterned embroidery applications to crinoline cheongsam dresses. This study uses the method of creation of work which is divided into four stages. The first is the pre-design stage. Second, the design stage. Third, the embodiment stage. Fourth, the presentation stage. This research resulted in the process of applying embroidery with dragon and phoenix motifs to the cheongsam crinoline dress starting from making the design, making and cutting the pattern, sewing the main material, sewing the crinoline by providing trim with tile cloth, attaching the crinoline to the cheongsam dress by tucking it tightly, then giving Embroidered patches with dragon and phoenix motifs by sewing using strings. The finished result is the application of embroidery with dragon and phoenix motifs on the crinoline cheongsam dress according to the design that has been made. With the characteristic selection of yellow color with dragon aAnd phoenix embroidery, it really describes the characteristics of Chinese Dress.AbstrakPenelitian ini bertujuan untuk mengetahui bagaimana proses dari penerapan aplikasi bordir bermotif naga dan burung phoenix pada crinoline dress cheongsam, dan mengetahui hasil penerapan aplikasi bordir bermotif naga dan burung phoenix pada crinoline dress cheongsam. Penelitian ini menggunakan metode penciptaan karya yang terbagi menjadi empat tahap. Pertama yaitu tahap pra-perancangan. Kedua, tahap perancangan. Ketiga, tahap perwujudan. Keempat, tahap penyajian. Penelitian ini menghasilkan proses penerapan aplikasi bordir bermotif naga dan burung phoenix pada crinoline dress cheongsam dimulai dari membuat desain, membuat dan memotong pola, menjahit bahan utama, menjahit crinoline dengan memberikan lis dengan kain tile, memasangkan crinoline pada dress cheongsam dengan dijelujur rapat, kemudian memberikan aplikasi bordir tempel bermotif naga dan burung phoenix dengan cara disum menggunakan senar. Hasil jadi penerapan aplikasi bordir bermotif naga dan burung phoenix pada crinoline dress cheongsam sesuai dengan desain yang telah dibuat. Dengan pemilihan karakteristik warna kuning dengan bordiran naga dan burung phoenix sangat menggambarkan karakteristik dari chinese dress.